Physicochemical Characteristics and Antimicrobial Efficacy of Soaps Prepared Using Carica papaya Extracts - Pednekar, S.; Mangaonkar, K. (Journal of Scientific Research, 2023)
Value-added products harnessing the phytotherapeutic potential of papaya are scarce. There is a paucity of data on the efficacy and safety of such products (if available) from papaya. Thus, the current study attempted to exemplify the utilization of papaya extracts in preparing a value-added product, namely, Toilet Soap. This study is the first of its kind in which the physicochemical characteristics and antimicrobial efficacy of the toilet soaps infused with different papaya extracts were assessed and compared against the market available soaps containing papaya fruit extract. The soap samples had pH values between 8.37 – 9.74 and their moisture content between 2.94 – 11.32 %. Their estimated lather volume ranged between 410 – 780 mL with good foaming power and foam stability. The laboratory-prepared soaps (Samples A to D) had matter insoluble slcohol and total fatty matter contents per Bureau of Indian Standards. They either did not contain or had an insignificant amount of free caustic alkali. The quantitative in vitro assessment findings showed antibacterial efficacy against Streptococcus aureus except for Sample E. The in vivo finger imprint test demonstrated the antibacterial efficacy of the soaps against E. coli and S. aureus.